2021
DOI: 10.1016/j.ssmph.2021.100764
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity, state fragility and youth mental health: A global perspective

Abstract: Youth in fragile settings face disproportionate risks of experiencing food insecurity and poor mental health. Cross-national evidence is lacking on the association between food insecurity and mental health in youth populations, and on state fragility as a social determinant of these experiences. We analysed data from six cycles of the Gallup World Poll (2014–2019), an annual survey that contains multi-item scales of food insecurity, mental health problems and positive wellbeing. The analytic sample included 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…For one, we observed a significant association between FI and poor mental health among youth globally. This result was in line with several previous analyses of GWP data, conducted among both youth [21,22] and adults [8,[49][50][51][52]. Our analysis controlled for a number of indicators of poverty and material deprivation, such as annual household income, education, and employment status.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…For one, we observed a significant association between FI and poor mental health among youth globally. This result was in line with several previous analyses of GWP data, conducted among both youth [21,22] and adults [8,[49][50][51][52]. Our analysis controlled for a number of indicators of poverty and material deprivation, such as annual household income, education, and employment status.…”
Section: Discussionsupporting
confidence: 89%
“…The association remained significant when the sample was stratified by country income level and UN sub-region. In their analysis of FI, state fragility, and mental health among youth, Elgar et al [22] also reported significant associations between FI and poor mental health across all UN sub-regions. These findings suggest that the FI-mental health relationship persists among youth across cultural contexts.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was reported years after that the number of undernourished people is still increasing world-wide by about five million each year with overwhelming majority in the developing world [ 3 ]. Unfortunately, the egg, which is a compact source of vital nutrients and should have been a more natural way of delivering the needed nutrients, is prohibitively expensive for the typical man.…”
Section: Introductionmentioning
confidence: 99%